Analisis Kapasitas dan Kinerja Saluran Drainase terhadap Perubahan Tata Guna Lahan Perkotaan - Cahyono, Christian; Miguez , Marcelo Gomes (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Urban land use change increases impervious surfaces and directly affects the capacity and performance of urban drainage channels. Many drainage systems are designed based on outdated land use conditions and fail to accommodate increased runoff due to rapid urbanization. This study aims to analyze drainage channel capacity and performance in response to urban land use change using an integrated hydrological and hydraulic approach. The method involves design rainfall analysis, runoff discharge estimation, and hydraulic capacity modeling using commonly applied urban drainage software. Performance evaluation is conducted by comparing existing channel capacity with design discharge for various return periods. The results indicate that most channels are unable to convey design discharge due to increased runoff coefficients caused by land use change. These findings are consistent with empirical studies showing that uncontrolled urbanization significantly elevates flood and inundation risks. The study concludes that channel capacity upgrading, green infrastructure integration, and alignment between land use planning and drainage design are essential to improve urban drainage system performance.